Produtividade e qualidade física e fisiológica de sementes de genótipos de alface produzidas sob o manejo orgânico - Josiany Thamara Alves Souza (2018)
In Brazil, a large part of the organic cultivation of vegetables is made with conventional seeds and, despite the demand, the supply of seeds in this system is still small, as are studies on the subject. The present study was developed to evaluate the productivity and seed quality of lettuce genotypes produced in two consecutive years in the organic management system. The work was conducted at the Instituto the Ciências Agrárias of the Universidade Federal the Minas Gerais. Two plantations were installed in open field conditions corresponding to the autumn / winter seasons in 2016 and 2017. Ten lettuce genotypes were evaluated, seven of them coming from the Embrapa Hortaliças germplasm bank and three from the local trade, in four replications, and organic management consisted of the use of a pig biofertilizer and the seeds were harvested manually. The following evaluations were performed: seed yield in kg ha-1; physical tests (degree of humidity and weight of 1000 seeds); germination and vigor test (first germination count, germination speed index and dry seedling mass). The data obtained were submitted to analysis of joint variance and in case of significant effect, according to the F test for treatments, the Scoot Knott test was used at 5% probability for grouping the means. The Cuban genotype and the two genotypes Grand Rapids superior productivity under the conditions tested. In 2016, the highest moisture levels were recorded in the seeds and, in 2017, the highest seed weights. Only the two Grand Rapids genotypes reached the minimum germination standard established for commercialization (80%). Vanda and AC 5058 presented better performance in the two years for the tests of vigor of IVG and first count of germination, and Cinderella for the test of dry mass of seedlings.